Evaluation of Socio-Economic and Medicinal Benefits of Picralima nitida in Ibadan South East Local Government Area, Oyo State, Nigeria - O. C. Odeyale; E. B. Olawuyi; A. S. Adetunji; O. A. Akeredolu (Journal of Applied Sciences and Environmental Management)
Picralima nitida is medicinal plant that is highly valued for its wide medicinal properties throughout its distribution areas. Hence, the objective of this paper is to evaluate the socio-economic and medicinal benefits of Picralima nitida in Ibadan South East Local Government Area, Oyo State, Nigeria using appropriate standard methods. Results showed that the respondents were dominated by females (86.0%), married (66.0%) with no formal education (29.0%).  Based on the likert scale rating, nine perceptional statements were agreed to except combining Picralima nitida with synthetic drug for use was disagreed to. Fourteen medicinal uses of Picralima nitida were identified. These included treatment of cancer, diabetes, fever, fibroid, gastrointestine, hypertension, jaundice, malaria, menstrual pain, pile, pneumonia, sexual weakness, stomach ache and typhoid with different methods of preparation and usage. The logit model showed that education and gender had the likelihood of significantly influencing the supply of honey at p<0.01. The study concluded that Picralima nitida have wide acceptability and perception among the population of study.